2000
DOI: 10.1080/030097400447688
|View full text |Cite
|
Sign up to set email alerts
|

Diet therapy for rheumatoid arthritis: A controlled double-blind study of two different dietary regimens

Abstract: Dietary manipulation, either by modifying food supplements or by reducing weight, may give some clinical benefit although no significant improvement can be observed assessing the results with a composite index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Studies have shown that Mediterranean or vegan diet reduces inflammatory activity, increases physical function, and improves vitality [ 19 ]. However, some other studies find benefits without achieving a significant improvement in composite indices to measure disease activity [ 81 , 82 ]. Nevertheless, in these studies, it has not been determined whether a rheumatoid arthritis improvement was actually due to a change in intestinal flora composition.…”
Section: Gut Microbiota In Rheumatoid Arthritismentioning
confidence: 99%
“…Studies have shown that Mediterranean or vegan diet reduces inflammatory activity, increases physical function, and improves vitality [ 19 ]. However, some other studies find benefits without achieving a significant improvement in composite indices to measure disease activity [ 81 , 82 ]. Nevertheless, in these studies, it has not been determined whether a rheumatoid arthritis improvement was actually due to a change in intestinal flora composition.…”
Section: Gut Microbiota In Rheumatoid Arthritismentioning
confidence: 99%